Caderneta de saúde da pessoa idosa no olhar dos profissionais da Estratégia de Saúde da Família - Sá, Célia Maria Cartaxo Pires de (2016)
The increasing population of over 60 year old people is one of the most expressive demographic phenomena in Brazil. That reality demands a different look in every instances of care. The health of the elderly is an strategic area of the basic attention, and the Ministry of Health has created the Health Book of the Elderly (Caderneta de Saúde da Pessoa Idosa) to identify the vulnerabilities and singularities of that people and thus, implement specific actions to minimize the grievances. Purpose: This study aims to identify the social depictions on the Health Book of the Elderly made by the professionals of basic attention. Methodology: It is an exploratory study, with a qualitative approach founded on the Theory of Social Depictions, made on the Family Health Units (Unidades de Saúde da Família) of the V Sanitation District in the city of Joao Pessoa-ParaibaBrazil, with 53 randomly chosen health professionals. The data have been collected from a semi structured interview, in two parts: the first one took into account Technique of free association of words (TALP), with the inductive term: Health Book of the Old Person(Caderneta de Saúde da Pessoa Idosa); the second one consisted of questions concerning the use of the Health book by the professional staff and social demographic information. The data collected from TALP have been processed with the help of the Iramutec software, version 0.7 alpha 2, and the open questions have analyzed through the Thematic Category Content Analyses Technique (Técnica de Análise de Conteúdo Temática). The material from the analyses of content showed six categories associated to Health Book of the old Person (Caderneta de Saúde da Pessoa Idosa), as follows: a) Tool for care; b) Instrument of self-sufficiency for the elderly; c) Information Resource about the health of the elderly; d) Working object; e) Follow up guide on the health of the elderly and f) Health support. Results: Among the interviewed people, 86,8% said that they use the Health Book for Old people; 3,8% said they don’t know it, and 9,4% said that they can have the Health book, but don’t use it. The professional staff represent the Health Book with contents predominantly positive, they link it to positive as well as negative images and are favorable to its use, for it contains important and valuable information to be considered when caring the elderly health care, to consolidate public health policies aiming an active and healthy aging. Conclusion: Impounding social representations built by the basic attention staff concerning the Health Book of the Elderly may contribute to substantiate discussions on increasing the number of elderly and professional staff using the health book a tool to promote better health to people on their aging process.